1998
DOI: 10.1093/nar/26.18.4153
|View full text |Cite
|
Sign up to set email alerts
|

Domain organization and functional analysis of Thermus thermophilus MutS protein [published erratum appears in Nucleic Acids Res 1998 Oct 15;26(20):following 4789]

Abstract: MutS protein binds to DNA and specifically recognizes mismatched or small looped out heteroduplex DNA. In order to elucidate its structure-function relationships, the domain structure of Thermus thermophilus MutS protein was studied by performing denaturation experiments and limited proteolysis. The former suggested that T. thermophilus MutS consists of at least three domains with estimated stabilities of 12.3, 22.9 and 30.7 kcal/mol and the latter revealed that it consists of four domains: A1 (N-terminus to r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 0 publications
0
15
0
Order By: Relevance
“…2 A). This doublet was shown to be essential for mismatch recognition and specific DNA binding activity (33,34). We were unable to detect three other conserved domains characteristic of MutS.…”
Section: Resultsmentioning
confidence: 61%
“…2 A). This doublet was shown to be essential for mismatch recognition and specific DNA binding activity (33,34). We were unable to detect three other conserved domains characteristic of MutS.…”
Section: Resultsmentioning
confidence: 61%
“…With T. aquaticus MutS, a similar apparent molecular mass of 280 kDa was reported by size-exclusion chromatography (16,31); however, by other physicochemical methods, the molecular mass was estimated to be about 180 kDa, which corresponds to a dimer (31). Recently, it has been reported that E. coli MutS exists as mixture of dimers and higher order forms (17). The N-terminal and central domains were constructed as His-tagged proteins, and the resultant proteins were designated as MutS-A and MutS-B, respectively.…”
Section: Construction Of Truncated Proteins Corresponding To Eachmentioning
confidence: 53%
“…Domain-As we have already shown, MutS protein can be divided into at least three domains based on the results of limited proteolysis and the denaturation (17). In order to analyze the functions of each domain in more detail, truncated proteins that correspond to the proteolytic fragments were designed (Fig.…”
Section: Construction Of Truncated Proteins Corresponding To Eachmentioning
confidence: 99%
See 2 more Smart Citations